Hydrogen oxidation on ordered intermetallic phases of platinum and tin – a combined experimental and theoretical study - Santos, Elizabeth del Carmen (2012)
Hydrogen oxidation on the surfaces of the intermetallic compounds Pt3Sn, PtSn and PtSn2 has been studied by the rotating disc electrode technique. Pt3Sn and PtSn were found to be good catalysts, about as good as Pt, while PtSn2 was inactive over the investigated range of potentials. Underpotential deposition of hydrogen is observed only on Pt3Sn. These results are explained by theoretical calculations based on a theory developed within our own group, and by density functional theory.